Suffering and damage in Catholic sexuality - Patton, Michael S. (Journal of religion and health, 1988)
This article suggests there may be a probable correlation between Catholic sexual orthodoxy and pathology in various Catholic cultures of the United States. There exists no empirically valid documentation suggesting the need for scientific research.In a series of private interviews conducted anonymously with religious and clinical professionals and a limited sample of lay opinion, there was near unanimous support for the idea of research linking sexual orthodoxy and pathology in the Catholic tradition, since the majority interviewed believe it is an undocumented fact based on clinical-pastoral observation and human experience.